The relationship between functional living status and perceived social support in patients with cancer - Seda Karaman; Elanur Yılmaz-Karabulutlu (Tehran University of Medical Sciences, 2016)
Background & Aim: Cancer is a significant and global health problem that negatively affects the functional status. The aim of this study was to investigate the relationship between perceived social support, functional status and demographic characteristics in cancer patients. Methods & Materials: : This cross-sectional study was conducted with 243 patients with cancer, who met the research criteria and got treatment in the medical oncology clinic and chemotherapy unit in 2011. In the research, "Patient Information Form" was used to identify the socio-demographic and medical characteristics of the patients, "Functional Living Scale (FLS) - Cancer" was used to assess their functional statuses, and "Cancer Patients Social Support Scale" was used to assess their perceived social support. Data analysis was performed by descriptive statistics tests, One -Sample T Test,  Kruskal-Wallis test, Pearson Correlation and regression test. The statistical significance level was determined as p<0.05. Results: In this study, there was positive correlation between perceived social support and functional living. There was statistically significant relationship between diagnosis and educational status with FLS. There was statistically significant relationship between age, gender, marital status, educational status, disease duration and social support. Conclusion: In this study, patients' functional living status improves as the perceived social support increases. Therefore, interventions to improve functional living status and social support of patients Can be synergistic.